Marginalizing and Distracting: Digital Technology Integration in Kurikulum Merdeka - Adara, Reza Anggriyashati; Victorynie, Irnie (Anaphora : Journal of Language, Literary, and Cultural Studies, 2025)
The implementation of Indonesia’s Kurikulum Merdeka aims to transform education through student-centered learning and digital technology integration. However, this study reveals significant challenges that hinder its success. Drawing on recent surveys, case examples, and literature, the findings highlight how economic and infrastructural barriers marginalize both teachers and students, limiting access to essential digital tools and reliable internet. Moreover, while digital technologies offer promising educational affordances, their use also introduces distractions that can undermine learning outcomes. These tensions expose a gap between the curriculum’s visionary goals and the practical realities faced in diverse educational contexts. The study underscores the urgent need for targeted policy interventions to improve digital equity, support teachers, and develop strategies to manage technology use effectively. Implications for curriculum design and recommendations for future research on digital inclusion and distraction management are discussed to guide the evolution of Kurikulum Merdeka towards a more equitable and effective education system.